CACHEXIA & BROWN FAT: A BURNING ISSUE IN CANCER - Kir, Serkan (Trends Cancer, 2016)
Cachexia, a progressive weight loss in cancer patients that results from tumor-induced energy wasting, is a serious problem that interferes with response to treatment and affects quality of life. Recent studies suggest that thermogenesis of adipose tissues is involved in energy wasting and also point to a link between the atrophy of fat and muscle. Tumor-derived PTHrP has emerged as a key molecule playing multiple roles in cachexia, from fat “browning” factor to potential therapeutic target.